2022
DOI: 10.1111/jfbc.14342
|View full text |Cite
|
Sign up to set email alerts
|

Probable mechanisms involved in the antiepileptic activity of Clerodendrum polycephalum Baker (Labiatae) leaf extract in mice exposed to chemical‐induced seizures

Abstract: The leaves of Clerodendrum polycephalum Baker (Labiatae) are used as a dietary legume supplement and applied ethnomedicinally for the management of epilepsy, convulsion, and spasms. This study is aimed at evaluating the effects of Clerodendrum polycephalum (CP) leaf extract on chemical‐induced seizures in mice and the possible mechanisms of action. Swiss albino mice were pretreated with CP (50, 100, or 500 mg/kg, p.o.) prior to intraperitoneal injection of picrotoxin (PTX) or pentylenetetrazole (PTZ). However,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…In the development of TLE, the involvement of OS and neuroinflammation have been well established as important factors, in part because the large amount of energy required by the brain is considered to be a possible mechanism involved in epileptogenesis [ 12 , 21 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 ]. In recent studies, it was observed that the specific inhibition of NADPH oxidase (NOX), the main producer of OS through O 2 •− synthesis, modified chronic epilepsy in a TLE rat model, preventing ROS generation, mitochondrial depolarization, and neuronal death.…”
Section: Discussionmentioning
confidence: 99%
“…In the development of TLE, the involvement of OS and neuroinflammation have been well established as important factors, in part because the large amount of energy required by the brain is considered to be a possible mechanism involved in epileptogenesis [ 12 , 21 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 ]. In recent studies, it was observed that the specific inhibition of NADPH oxidase (NOX), the main producer of OS through O 2 •− synthesis, modified chronic epilepsy in a TLE rat model, preventing ROS generation, mitochondrial depolarization, and neuronal death.…”
Section: Discussionmentioning
confidence: 99%